The Ukraine Conflict and its Resonance in the European Real Estate Market: Geopolitical Turning Points of the 21st Century and their Real Estate Echo Effects - Norman SCHERER (Communications of International Proceedings, 2023)
This paper examines the geopolitical dynamics of the 21st century, highlighting the global impact of regional conflicts exemplified by Russia's invasion of Ukraine. Recognised as a major conflict since March 2022, the conflict has not only triggered a significant refugee crisis, but has also created significant economic, social and humanitarian challenges that have equally particularly affected the European real estate sector. The invasion is referred to as a "black swan" event. The study examines the impact of the Ukraine conflict on the European real estate market, focusing on the resilience of the market, the opportunities and risks, and the appropriate responses of investors to such unforeseen events. The study uses the DiPasquale-Wheaton model as a theoretical framework to analyse the interaction between the real estate and rental markets and provide insights into their responses to exogenous shocks such as sudden immigration. However, the limitations of the model are acknowledged as it provides a simplified representation of reality and may not properly capture the dynamic evolution of the market after the shock or short-term responses. The paper emphasises the need for caution and prudence in investment decisions to avoid panicky market reactions and potential liquidity shortages. It argues for a deeper understanding of the intricate relationships between geopolitical events and the real estate industry in a globalised European context and highlights the complex valuation issues involved in multi-asset class allocations involving real estate. Ultimately, the study calls for a reassessment of asset allocation in light of new geopolitical risks, using the DiPasquale-Wheaton model as a valuable tool to illustrate the dynamic interplay between real estate and rental markets and to guide investment decisions amid uncertainty.
Keywords: Ukraine conflict; External shocks; European real estate industry; Liquidity crunch